Échanges internationaux en Europe et apprentissages - Magali Ballatore (Les éditions de la Maison des sciences de l'Homme, 2011)
The ERASMUS program (EuRopean community Action Schema for the Mobility of University Students) was launched in 1987 to facilitate student mobility and to mutually recognize diplomas throughout Europe. The latter goal of diploma recognition has largely diminished in recent years. How can higher education institutions utilize this supporting mechanism and what students take advantage of study abroad opportunities? Does the ERASMUS program democratize student mobility and accessibility as well as the possibilities associated with them? The increase in the number of study abroad options seems to accelerate the movement of specialized social academic streams and destinations. Far from the program's guiding principles, this article attempts to empirically respond to the above questions to see whether the ERASMUS rhetoric is actually delivered in practice? The international comparative case study of this research will demonstrate that the ERASMUS program tends to create insidious competition at the heart of national European institutions of higher learning as evidenced by the choices of university professors and students.